The Influence of Leadership and Compensation on Job Satisfaction: A Case Study of a Private Plantation Company in West Kalimantan - Aprila Marshanda Saputri (Journal of Business Economics : Needs, Services, and Money, 2025)
This study aims to examine the effect of leadership and compensation on employee job satisfaction at a private plantation company in Landak Regency, West Kalimantan. Using a quantitative approach, data were collected from 54 field supervisors through questionnaires, interviews, and observation. The results were analyzed using multiple linear regression with SPSS 26. The findings indicate that compensation has a significant positive effect on job satisfaction, while leadership has a significant but negative effect. The adjusted R² value of 0.246 suggests that leadership and compensation together explain 24.6% of the variance in job satisfaction. The negative impact of leadership implies a mismatch between current leadership practices and employee expectations, potentially resulting in decreased satisfaction. Meanwhile, compensation appears to play a more critical and motivating role. These findings highlight the importance of revisiting leadership approaches and ensuring fair, transparent compensation systems to improve employee well-being and performance. Further research is recommended to explore additional variables influencing job satisfaction, such as organizational culture, workload, and career development opportunities. This study contributes to a deeper understanding of the human resource challenges faced by plantation-based organizations in Indonesia